SIRT1 activation and its effect on intercalated disc proteins as a way to reduce doxorubicin cardiotoxicity - Podyacheva, Ekaterina; Toropova, Yana (Frontiers in Pharmacology, 2022)
According to the World Health Organization, the neoplasm is one of the main reasons for morbidity and mortality worldwide. At the same time, application of cytostatic drugs like an independent type of cancer treatment and in combination with surgical methods, is often associated with the development of cardiovascular complications both in the early and in the delayed period of treatment. Doxorubicin (DOX) is the most commonly used cytotoxic anthracycline antibiotic. DOX can cause both acute and delayed side effects. The problem is still not solved, as evidenced by the continued activity of researchers in terms of developing approaches for the prevention and treatment of cardiovascular complications. It is known, the heart muscle consists of cardiomyocytes connected by intercalated discs (ID), which ensure the structural, electrical, metabolic unity of the heart. Various defects in the ID proteins can lead to the development of cardiovascular diseases of various etiologies, including DOX-induced cardiomyopathy. The search for ways to influence the functioning of ID proteins of the cardiac muscle can become the basis for the creation of new therapeutic approaches to the treatment and prevention of cardiac pathologies. SIRT1 may be an interesting cardioprotective variant due to its wide functional significance. SIRT1 activation triggers nuclear transcription programs that increase the efficiency of cellular, mitochondrial metabolism, increases resistance to oxidative stress, and promotes cell survival. It can be assumed that SIRT1 can not only provide a protective effect at the cardiomyocytes level, leading to an improvement in mitochondrial and metabolic functions, reducing the effects of oxidative stress and inflammatory processes, but also have a protective effect on the functioning of IDs structures of the cardiac muscle.